Short-term effects of solar storms in phytoplankton photosynthesis - López Águila, Madeleine.; Rodríguez López, Lien.; González Rodríguez, Lisdelys.; Cárdenas, Rolando (Springer, 2023)
The potential short-term influence of a solar radiation storm on microalgal photosynthesis is investigated. We focus on muons from the secondary cosmic rays at sea level, given their high penetrating power. According to NOAA’s classification of solar radiation storms, two kinds of solar storms are considered: moderate/strong and extreme. An exponential decay of muon fluxes down the water column and a direct proportionality between their penetrating power and energy are assumed. This allows obtaining a function of ionizing radiation to be embedded in a physical-mathematical model for photosynthesis previously modified by some of us to include particulate ionizing radiation. It is shown that moderate/strong solar radiation storms can cause a short-term depletion of photosynthesis of up to 61%, while this figure scales to 75% for extreme storms.
Keywords: Radiación ionizante; Muones; Fotosíntesis